The Impact of Beamforming, Power Control, and Sectorization on CDMA Capacity - Linna Oktaviana Sari (UIN Sultan Syarif Kasim Riau, 2011)
Capacity of CDMA was limited by interferences and could be optimalyzed by reduce interferences to fulfill requirements of multiclass services. In this research, the impact of imperfect power control and imperfect sectorization to reverse-link user capacity of CDMA system based on signal to interference ratio (SIR) by using beamforming at mobile station transmitter and base station receiver have been analyzed. Beamforming would be used with assumed each element has uniformly excited, equally spaced linear array. CDMA system use hexagonal macro cell in home cell base station, which divided effectively into 3 sectors with 120o beam width. User capacities was influenced by power control factor, number of antenna beamforming elements and sectors, overlap angle due to imperfect sectorization, imperfect power control, SIR and processing gain CDMA. Results of this research indicate that the system with power control and sectorization using beamforming has larger capacity of multiclass system than without beamforming. Keywords: Beamforming, Power Control, Sectorization, Multiclass, CDMA.